2021
DOI: 10.1088/1742-6596/1795/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crosslinking agent (glutaraldehyde) on the mechanical properties of (PVA/Starch) blend and (PVA/PEG) binary blend films

Abstract: This paper displays the effect of glutaraldehyde (GA) as a crosslinking agent with different weight ratios (5,8 and 10%) on the mechanical properties (elongation at break and tensile strength) of polyvinyl alcohol/starch & polyvinyl alcohol / polyethylene glycol blend. Solution casting technique was used to prepare (75%PVA/25%corn starch), and (75% PVA/25% PEG) blend films. The results confirmed that when the increased concentration of GA, the tensile strength increased, while elongation at break decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…GTA was used as a crosslinking agent to improve the handling properties of the films. This can be reasoned to reduced mobility of the polymer chains due to the crosslinking reaction, which increased the films’ tensile strength [ 38 ]. The physical and mechanical properties of the PVA/ cellulose film were significantly improved upon GTA addition [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…GTA was used as a crosslinking agent to improve the handling properties of the films. This can be reasoned to reduced mobility of the polymer chains due to the crosslinking reaction, which increased the films’ tensile strength [ 38 ]. The physical and mechanical properties of the PVA/ cellulose film were significantly improved upon GTA addition [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study also provides a facile framework to manufacture hydrogel-reinforced hydrogels with hierarchical structures to achieve increased tensile and mechanical properties whilst retaining the high-equilibrium water content similar to those seen in native human tissues. Studies where hydrogel strengths exceeded 1 MPa have used either chemical crosslinking [ 39 , 40 , 41 ] or other more complex methods such as freeze-casting [ 42 ], freeze-assisted salt-leaching [ 42 ], or molecular self-assembly [ 43 ]. This study would be useful as a reference for future studies wanting to engineer strong hydrogel constructs to repair or replace soft tissues in humans.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the tensile strength of the plastics prepared using rice starch cross-linked with 1%, 2% and 3% of STMP were 6.3, 7.23 and 8.23 MPa, respectively. Musa and Hameed (2021) The effect of the cross-linking agent on the tensile strength of the plastics is related to the reinforcement effect of the cross-linking. One molecule of cross-linking agent connects two molecules of amylose or amylopectin.…”
Section: Tensile Strengthmentioning
confidence: 99%